Interspecific Gene Exchange Introduces High Genetic Variability in Crop Pathogen. (11th October 2019) - Feurtey, Alice; Stevens, Danielle M; Stephan, Wolfgang; Stukenbrock, Eva H
Abstract: Genome analyses have revealed a profound role of hybridization and introgression in the evolution of many eukaryote lineages, including fungi. The impact of recurrent introgression on fungal evolution however remains elusive. Here, we analyzed signatures of introgression along the genome of the fungal wheat pathogen Zymoseptoria tritici . We applied a comparative population genomics approach, including genome data from five Zymoseptoria species, to characterize the distribution and composition of introgressed regions representing segments with an exceptional haplotype pattern. These regions are found throughout the genome, comprising 5% of the total genome and overlapping with > 1, 000 predicted genes. We performed window-based phylogenetic analyses along the genome to distinguish regions which have a monophyletic or nonmonophyletic origin with Z. tritici sequences. A majority of nonmonophyletic windows overlap with the highly variable regions suggesting that these originate from introgression. We verified that incongruent gene genealogies do not result from incomplete lineage sorting by comparing the observed and expected length distribution of haplotype blocks resulting from incomplete lineage sorting. Although protein-coding genes are not enriched in these regions, we identify 18 that encode putative virulence determinants. Moreover, we find an enrichment of transposable elements in these regions implying that hybridization may contribute to the horizontal spread of transposable elements. We detected a similar pattern in the closely related species Zymoseptoria ardabiliae, suggesting that hybridization is widespread among these closely related grass pathogens. Overall, our results demonstrate a significant impact of recurrent hybridization on overall genome evolution of this important wheat pathogen.